ENRICHMENT OF THE COMPOSITION OF YOGURT: THE USE OF BIOLOGICALLY ACTIVE FOOD ADDITIVES BASED ON SPROUTED WHEAT AND BARLEY - I. R. Askarov; D. T. Khasanova (American Journals Publishing, 2024)
This article delves into a transformative approach to yogurt enrichment, exploring the incorporation of biologically active food additives derived from sprouted wheat and barley. The significance of these additives in enhancing the nutritional profile of yogurt is elucidated, emphasizing the unique contributions of sprouted grains. The article provides insights into the preparation and utilization of these biologically active additives, offering a practical guide for enriching yogurt at home. Through a combination of nutritional science and culinary innovation, this research opens a flavorful pathway to elevate yogurt's health benefits, establishing a connection between dairy products and the wholesome goodness of sprouted wheat and barley.
Keywords: Yogurt Enrichment, Biologically Active Food Additives, Sprouted Wheat, Sprouted Barley, Nutritional Enhancement, Dairy Innovation, Culinary Health, Functional Foods, Yogurt Composition, Homemade Enrichment.